Linking social, ecological, and physical science to advance natural and nature‐based protection for coastal communities. Issue 1 (30th March 2017) - Arkema, Katie K.; Griffin, Robert; Maldonado, Sergio; Silver, Jessica; Suckale, Jenny; Guerry, Anne D.
Abstract : Interest in the role that ecosystems play in reducing the impacts of coastal hazards has grown dramatically. Yet the magnitude and nature of their effects are highly context dependent, making it difficult to know under what conditions coastal habitats, such as saltmarshes, reefs, and forests, are likely to be effective for saving lives and protecting property. We operationalize the concept of natural and nature‐based solutions for coastal protection by adopting an ecosystem services framework that propagates the outcome of a management action through ecosystems to societal benefits. We review the literature on the basis of the steps in this framework, considering not only the supply of coastal protection provided by ecosystems but also the demand for protective services from beneficiaries. We recommend further attention to (1) biophysical processes beyond wave attenuation, (2) the combined effects of multiple habitat types (e.g., reefs, vegetation), (3) marginal values and expected damage functions, and, in particular, (4) community dependence on ecosystems for coastal protection and co‐benefits. We apply our approach to two case studies to illustrate how estimates of multiple benefits and losses can inform restoration and development decisions. Finally, we discuss frontiers for linking social, ecological, and physical science to advance natural and nature‐based solutions to coastal protection.